PRAKTIK BLENDED LEARNING BERBASIS MODERASI ISLAM DALAM PENDIDIKAN ANAK USIA DINI DI MASA PANDEMI COVID-19 - Budiman Pohan; Tiara Khoerunnisa (Balai Diklat Keagamaan Bandung, 2021)
This study aims to determine the practice of Islamic moderation-based on blended learning in early childhood education during Covid-19 pandemic. This study uses a qualitative method with case study design. Informants were selected purposively including educators, students, and parents. Data collection was carried out by observation, interviews, and documentation. Data analysis took place in stages, involving collection, exposition, reduction, verification, and data conclusion, as well as triangulating the data sources. The results show that the learning formats at Al-Munar Kindergarten were in form of: 1) adaptive, the availability of required learning model options; 2) communicative, direct or virtual communication between school and students; 3) technology, learning media and digital platforms utilization; 4) innovative, virtual performance; and 5) facilitative, provided learning equipment by the school. The disposition of Islamic moderation is in form of discursive awareness manifested in oral religious understanding and practical awareness through daily ‘adab’ for students.Keywords: Blended Learning; Islamic Moderation; Early Childhood Education; COVID-19 Pandemic.